Stable p-type nitrogen-doped zinc oxide films prepared by magnetron sputtering. (October 2020) - Chen, J.Y.; Zhang, H.T.; Chen, Q.; Husian, F.; Cherng, Jyh-Shiarn
Abstract: P-type nitrogen-doped zinc oxide (NZO) thin film was prepared on a glass substrate by reactive magnetron sputtering using zinc metal target and O2 /N2 atmosphere. The structural, electrical and optical properties of the NZO films were investigated by X-ray diffraction, electron microscopy, Hall-effect, and Raman scattering measurements. The electrical properties of the optimized p-type NZO films showed a resistivity of 13.1 Ω-cm and an n-p-n transition of conduction mode with increasing nitrogen flow rate was observed. This transition can be ascribed to the two types of defects, NO, N substitutes for an O site, and (N2 )O, N2 substitutes for an O site, due to nitrogen doping as verified by X-ray photoelectron spectroscopy. This sputtering process was reproducible and effective in producing p-type NZO films, and the produced p-type NZO was stable in a period of 259 days after deposition. Highlights: P-type nitrogen-doped zinc oxide thin films were prepared by reactive RF sputtering. The p-type films showed a resistivity of 13.1 Ω-cm. An n-p-n transition of conductivity with nitrogen flow rate was observed. This transition was ascribed to NO and (N2 )O verified by XPS and Raman. The p-type conductivity was stable in a period of 259 days after deposition.